PENGARUH BRAND AMBASSADOR DAN SOCIAL MEDIA MARKETING TERHADAP MINAT BELI PADA PRODUK MCDONALD’S - Selia (PT Naureen Digital Education, 2024)
This research was conducted to find out how much influence brand ambassadors and social media marketing have on the buying interest of 6th semester IMWI students majoring in Management on McDonald's products. The research method used is a quantitative method approach with data collection techniques using saturated samples or non-probability sampling where the entire population is used as a sample. The population in question is all 6th semester IMWI students majoring in Morning Regular Management who have purchased McDonald's products at least once, totaling 63 respondents using a questionnaire on a Likert scale. In processing data for analysis using SPSS 29.0.2.0 software with multiple linear analysis techniques which include validity tests, reliability tests, and classical assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity tests, then hypothesis tests consisting of t tests, f and coefficient of determination test. This research shows that there is a positive and significant influence, both partially and simultaneously, between the brand ambassador and social media marketing variables on purchase interest in McDonald's products.